Air‐Stable Solar Cells with 0.7 V Open‐Circuit Voltage Using Selenized Antimony Sulfide Absorbers Prepared by Hydrazine‐Free Solution Method. Issue 5 (14th February 2019) - Cheng, Jiang; Hu, Rong; Wang, Kun; Meng, Xiang; Li, Ying; Yang, Xin; Liao, Xiaoqing; Li, Lu; Chong, Kok Boon
Abstract : Antimony chalcogenide is a promising absorber material for photovoltaic (PV) cells because of its tunable band gap, strong optical absorption, earth‐abundant, and nontoxic constituents. Here, a novel hydrazine‐free approach for fabricating antimony chalcogenide films prepared via spray pyrolysis deposition with further selenylation, as well as high performance solar cells are reported. The fabricated antimony chalcogenide solar cells exhibits remarkably high open‐circuit voltage ( V OC ) comparing with that of Sb2 Se3 and Sb2 S3 devices. The distribution of Se during the selenylation process via refering to the Fick's second law is discussed. The results show that the selenized absorber has tremendously improved absorbance for visible light and a cascade‐type energy level from surface to bulk, resulting in an ideal energy level matching for p‐n junction. By introducing an efficient buffer layer, the detrimental short‐circuit is avoided by reducing the cracks. Finally, 4.57% of the power conversion efficiency (PCE) of the solar cell is achieved. Furthermore, a module with a large‐scale active area of 21 cm 2 is successfully fabricated, which shows a PCE of 3.19%, and a V OC of 3.42 V. The present work suggests that the antimony chalcogenide solar cells are promising for industrial application. Abstract : Antimony chalcogenide is a promising absorber material for photovoltaic cell. The authors achieve a power conversion efficiency (PCE) of 4.57% for spray coated Sb2 (S1‐x Sex )3 film solar cells with a post selenylation and prepare a module with a large‐scale active area of 21 cm 2 with a PCE of 3.19%，suggesting this technique is promising for industrial application.